Discreding as one of the KGB`s Methods of Forming Public Opinion - Burinskaitė, Kristina (Genocidas ir rezistencija, 2006)
From the 1950s onwards, the KGB was increasingly using psychological measures in addition to physical repression in its fight against the anti–Soviet movement. At that time the Soviet security services were striving not only to deal with the opponents, but also to depict their activities to the public in a negative light, thus hoping to reduce the number of supporters of opponents and to justify repression against them. Compromising information and disinformation were among the most important tools to fight against internal and external enemies. The KGB devoted considerable attention and resources to compromising and disinformation campaigns aimed at misleading and harming internal and external enemies. Compromising campaigns were more political in nature and targeted the opposition, while disinformation campaigns were more economic and military and targeted foreign intelligence. The aim of all these campaigns was to secure the Communist Party’s power and control domestically and its economic–military power internationally.